Odpowiedzi

2009-11-24T19:41:28+01:00
Wykorzystujemy wzór: (a-b)(a+b) = a² - b²

1.
√7/2 + 1/2

2.
4 - 2√2

3.
-√6 - 2√2 - 2√3 - 4

4.
5 + 2√5

5.
3√6 + 7
2009-11-24T19:48:20+01:00
Wyniki wychodzą takie, a nie inne, ponieważ (a+b)*(a-b) = a²-b²

3 / √7-1 * √7+1/√7+1 = (3√7+3) / 6
2√2 /√2+1 * √2-1/√2-1 = 4-2√2
√2+2 / √3-2 *√3+2/√3+2 = -√6 -2√2 -2√3 -4
5+√5 / 3-√5 * 3+√5/3+√5 = 5-√5/2
4+√6 / √6-2 * √6+2/√6+2 = 3√6+7
2009-11-25T00:10:05+01:00
3 (√7+1)/ (√7-1) * (√7+1) = (3√7+3) / 6
2√2(√2-1) /(√2+1) * (√2-1) = 4-2√2
(√2+2)(√3+2) / (√3-2) *(√3+2) = -√6 -2√2 -2√3 -4
(5+√5) ( 3+√5)/( 3-√5) *(3+√5) = (15+5√5+3√5+5)/4=5+2√5
(4+√6) (√6+2)/( √6-2) * (√6+2) =(4√6+8+6+2√6)/2= 3√6+7